ANALISIS PENGARUH PERSEPSI EFEKTIFITAS REGULASI SISTEM PERPAJAKAN, TINGKAT KEPERCAYAAN PADA SISTEM PEMERINTAHAN DAN HUKUM PERPAJAKAN, UNDERSTANDING PUBLIC DAN SELF ASSESMENT SYSTEM TERHADAP WILLINGNESS TO PAY TAX (Studi Empiris Pada Kantor KPP Pratama Dua - Junaidi, Ahmad junaidi; sherly, Sherly oktaviani; Rina, Rina Yuniarti (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
This study is a quantitative descriptive study that aims to determine the effect of the perspective of the effectiveness of taxation system regulations, the level of trust in the government system and tax law, public understanding and self-assessment system on willingness to pay tax. This study was conducted at the KPP Pratama Dua Office of Bengkulu Province from November to December 2024. Sample was 394 people taken using accidental sampling, which means that every taxpayer who carries out Tax administration at the Pratama Tax Office in Bengkulu City who meets the researcher can be used as a respondent. Then the data that has been collected is tested with the help of the SPSS.20 application program with its validity and reliability analysis. The results of the study show that (1). The perspective of the effectiveness of taxation system regulations has an effect on willingness to pay tax, (2). The level of trust in the government system and tax law influences the willingness to pay tax, (3). Public understanding influences the willingness to pay tax, (4). The self-assessment system influences the willingness to pay tax